The influence of serial fecal sampling on the diagnosis of giardiasis in humans, dogs, and cats - Flávia Fernandes de Mendonça Uchôa; Adriana Pittella Sudré; Daniel de Barros Macieira; Nádia Regina Pereira Almosny (Revista do Instituto de Medicina Tropical de São Paulo, 2017)
ABSTRACT Giardia infection is a common clinical problem in humans and pets. The diagnosis of giardiasis is challenging as hosts intermittently excrete protozoan cysts in their feces. In the present study, we comparatively evaluated two methods of serial fecal sampling in humans, dogs, and cats from Rio de Janeiro, Brazil. The Faust et al. technique was used to examine fecal specimens collected in triplicate from 133 patients (52 humans, 60 dogs, and 21 cats). Specimens from 74 patients were received from the group assigned to carry out sampling on consecutive days - 34 humans, 35 dogs, and 5 cats, and specimens from 59 patients were received from the group assigned to carry out sampling on non-consecutive, separate days - 18 human beings, 25 dogs, and 16 cats. G. duodenalis cysts were found in stools of 30 individuals. Multiple stool sampling resulted in an increase in the number of samples that were positive for Giardia in both groups. The authors therefore conclude that multiple stool sampling increases the sensitivity of the Faust et al . technique to detect G. duodenalis cysts in samples from humans, cats and dogs.